2010
DOI: 10.4319/lom.2010.8.0575
|View full text |Cite
|
Sign up to set email alerts
|

Improving the accuracy of four‐receiver acoustic Doppler velocimeter (ADV) measurements in turbulent boundary layer flows

Abstract: Acoustic Doppler instrument measurements suffer from random spikes and Doppler noise. Using a fourreceiver ADV (acoustic Doppler velocimeter; Vectrino manufactured by Nortek) that allows recording beam velocities, we combine a spike-removal procedure on the beam velocities with a noise-reduction method on the flow velocities to improve turbulence measurements. We compare the results with those obtained from ADVP (acoustic Doppler velocity profiler) measurements under the same conditions, i.e., in turbulent ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…Due to their sampling geometry, the Vectrino+ ADVs provide very accurate measurements of vertical velocity ( w ), compared to the horizontal components. Theoretically, the noise level of the vertical velocity components is 13.9 times lower than the noise level of the horizontal velocity component in a four‐beam ADV [ Doroudian et al ., ]. While the accuracy of horizontal velocities is quoted as ± 1 mm s −1 [ Nortek, ], the vertical velocity has been estimated to have an accuracy of at least 10 times better, i.e., ±0.1 mm s −1 [ Devi and Kumar, ].…”
Section: Methodsmentioning
confidence: 99%
“…Due to their sampling geometry, the Vectrino+ ADVs provide very accurate measurements of vertical velocity ( w ), compared to the horizontal components. Theoretically, the noise level of the vertical velocity components is 13.9 times lower than the noise level of the horizontal velocity component in a four‐beam ADV [ Doroudian et al ., ]. While the accuracy of horizontal velocities is quoted as ± 1 mm s −1 [ Nortek, ], the vertical velocity has been estimated to have an accuracy of at least 10 times better, i.e., ±0.1 mm s −1 [ Devi and Kumar, ].…”
Section: Methodsmentioning
confidence: 99%
“…The ADV data were initially filtered using a correlation threshold of 0.4 [Martin et al, 2002;Strom and Papanicolaou, 2007], a signal-to-noise (SNR) ratio of 10 [Wahl, 2000;Strom and Papanicolaou, 2007], and the expected measurement range. Further removal of spikes caused by aliasing was achieved by removing all velocity measurements that fell outside 3 standard deviations of the mean and then recalculating and repeating this step once [Buffin-Bélanger et al, 2006;Doroudian et al, 2010].…”
Section: Velocity Datamentioning
confidence: 99%
“…Turbulence measurements are not only affected by Doppler noise, but also by random spikes. In contrast with Doppler noise, random spikes are not inherent to the measurement technique and occur mostly in poor measurement environments (Doroudian et al, 2010). To reduce the effect of noise resulting from random spikes, several post-processing filters have been proposed with the aim of improving the turbulence statistics measured by ADVs.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…It was shown that the modified method improved the spectrum over all frequencies compared to the original despiking method. Spike-removal, however, depends on the flow conditions and caution should be taken when proposing universal guidelines (Doroudian et al, 2010). Chanson et al (2008) used an ADV for high-frequency velocity measurements in a small estuary.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%